Analisis Pengaruh Sanksi Administrasi, Tingkat Pendapatan, Dan Sistem Samsat Drive Thru Terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor - Prita Oktavianty Puteri; Efrizal Syofyan; Erly Mulyani (Universitas Negeri Padang, 2019)
This study aims to find out empirical evidence whether there are effects of administrative sanctions, income levels, and SAMSAT drive thru on motor vehicle taxpayer compliance with empirical studies at the SAMSAT Office in Padang City. This research is a causative study. The population of this study is a motor vehicle taxpayer registered at the SAMSAT office in Padang City. The research sample was determined by slovin formula. The type of data used is subject data. The analytical method used is descriptive analysis and multiple regression analysis. The results of this study prove that there is a significant effect of administrative sanctions on motor vehicle taxpayer compliance, but the level of income and SAMSAT drive thru has no significant effect on motor vehicle taxpayer compliance.